2019
DOI: 10.3390/coatings9100598
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Creep Behavior Characterization of Single Crystal Superalloy by UV-DIC at 980 °C

Abstract: High temperature creep resistance is a critical characteristic of Ni-based single crystal (SX) superalloys. In this work, the creep behavior of a Ni-based SX superalloy was in situ characterized at 980 °C by ultraviolet (UV) imaging combined two-dimensional digital image correlation (DIC) in vacuum environment. The surface pattern was fabricated to maintain stable over 65 h at 980 °C. The pattern images captured by UV imaging were analyzed using mean gray value and the full-field strain map of creep deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Zheng et al [10] measured the influence of cyclic thermal loading on the fatigue creep behavior of pure copper specimens using DIC technology and found that under certain loads, an increase in the temperature rise rate caused the pure copper specimen to enter the fast creep stage earlier. Shang and Dong [11,12] utilized the full-field capability of UV-DIC technology to characterize the creep behavior of nickel-based superalloys and demonstrated the superiority of the DIC method. However, due to off-plane displacement and lens distortion, the measurement system error of the 2D-DIC method is difficult to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [10] measured the influence of cyclic thermal loading on the fatigue creep behavior of pure copper specimens using DIC technology and found that under certain loads, an increase in the temperature rise rate caused the pure copper specimen to enter the fast creep stage earlier. Shang and Dong [11,12] utilized the full-field capability of UV-DIC technology to characterize the creep behavior of nickel-based superalloys and demonstrated the superiority of the DIC method. However, due to off-plane displacement and lens distortion, the measurement system error of the 2D-DIC method is difficult to overcome.…”
Section: Introductionmentioning
confidence: 99%